PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN JASA PENGIRIMAN PT. AGILITY INTERNASIONAL - Dimas Panji Fikri Pratama; Arief Rachmawan Assegaf (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2023)
The research aimed to analyze the influence of service quality and company image on the customer service delivery loyality of PT. Agility Internasional. This study describes the causal relationship between service quality and corporate image on customer loyalty. The population in this study are customers of PT. Agility Internasional. Metode analys was taken using regression of simple and multiple linier analysis. The findings of this research indicated that Service quality corporate image has positive and significant with customer loyalty in PT. Agility Internasional.